Bridging the Divide: Does Social Capital Moderate the Impact of Polarization on Health?. (September 2022) - Panagopoulos, Costas; Fraser, Timothy; Aldrich, Daniel P.; Kim, Daniel; Hummel, David
Rising partisan polarization in the American public over the last decade has been linked to stress and anxiety, raising questions about how communities and public health experts should respond. As the strength of an individual's social network correlates with better health outcomes, could building a diverse set of connections moderate the effect of political polarization on an individual's health? This study examines the role of social capital as a key intervening variable in the relationship between polarization and health. Drawing on a nationally representative survey of 2, 752 U.S. residents conducted in December 2019 compared with county-level data, we use negative binomial, logit, and gamma models to examine the interaction between indicators of political polarization and bonding, bridging, and linking social capital on physical and mental health outcomes. We find consistent evidence that bonding social ties intervene to improve the physical and mental health of individuals in polarized communities, while bridging ties are related to worse health for politically isolated residents. By highlighting the relationship between polarization, social networks, and health, our findings shed light on how public health experts, and policymakers can improve health outcomes in polarized communities.